Dengue outbreak in the times of COVID-19 pandemic: Common myths associated with the dengue. (September 2022) - Zaheer, Saba; Tahir, Muhammad Junaid; Ullah, Irfan; Ahmed, Ali; Saleem, Sheikh Mohd; Shoib, Sheikh; Asghar, Muhammad Sohaib
Abstract: With the sharp rise in dengue cases across the state and the ongoing COVID-19 pandemic, it is crucial to pay attention to the common misbelieves among the population about dengue. It should be considered to actively spread awareness about the disease to bust the common myths associated with it. A few common myths include that it is a contagious disease, or it is a milder infection than COVID-19, so it's not taken more seriously, or that one cannot be coinfected with both dengue and COVID-19 at one time. We propose that accurate information about dengue can be spread through community education through televisions and social media to cater to the targeted audience. In addition to that, awareness campaigns in rural areas should be planned to help the masses understand the pathogenesis of the diseases and play a role in limiting the transmission.